BRCA Previvors: Medical and Social Factors That Differentiate Them From Previvors With Other Hereditary Cancers - Campo-Engelstein, Lisa (BioéthiqueOnline, 2017)
In this paper, I outline some of the reasons why BRCA “previvors” (i.e., “survivors of a predisposition to cancer”) are different from previvors with other hereditary cancers. I examine how the absence of a standard of care for breast cancer risk for women with a BRCA mutation, coupled with a broad range of genetic penetrance and lower mortality, makes BRCA different than other hereditary cancers that have clear and established guidelines. In addition to these medical differences, social factors like the cultural prominence of breast cancer and the social significance of breasts have engendered a more complicated individual previvor identity for and cultural response to women with a BRCA mutation.